2021
DOI: 10.1007/s00787-021-01797-4
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning and stimulus generalization in association with age in children and adolescents

Abstract: The aim of the study was to investigate age-related differences in fear learning and generalization in healthy children and adolescents (n = 133), aged 8–17 years, using an aversive discriminative fear conditioning and generalization paradigm adapted from Lau et al. (2008). In the current task, participants underwent 24 trials of discriminative conditioning of two female faces with neutral facial expressions, with (CS+) or without (CS−) a 95-dB loud female scream, presented simultaneously with a fearful facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
3
4
0
Order By: Relevance
“…This is in line with evidence in healthy populations showing steeper, i.e. more discriminative, generalization gradients in older compared to younger individuals ( Glenn et al, 2012 , Klein et al, 2021 , Reinhard et al, 2021 , Schiele et al, 2016 ). Discrimination performance, as assessed by the PM-Task, improved after compared to before conditioning (see also Roesmannet al, 2022a ), yet, we found no evidence for age-related group differences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with evidence in healthy populations showing steeper, i.e. more discriminative, generalization gradients in older compared to younger individuals ( Glenn et al, 2012 , Klein et al, 2021 , Reinhard et al, 2021 , Schiele et al, 2016 ). Discrimination performance, as assessed by the PM-Task, improved after compared to before conditioning (see also Roesmannet al, 2022a ), yet, we found no evidence for age-related group differences.…”
Section: Discussionsupporting
confidence: 91%
“…In most outcome measures, – with the exception of UCS expectancy ratings – adolescents showed generalization gradients similar to those observed in adults. This points towards a rather advanced developmental stage in adolescents, in line with findings of a more adult-like generalization pattern in older versus younger children ( Glenn et al, 2012 ) and steeper generalization gradients in healthy adolescents compared to children ( El-Bar et al, 2017 , Reinhard et al, 2021 ). In addition to the interpretation that adolescents achieved a level of development that is comparable with adults (in many respects), the lack of group differences in fear ratings might also be grounded in the overall rather low fear ratings - even in response to the CS+ .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, the age pattern reported by other researchers, with younger children displaying more fears than older children (KUSHNIR;SADEH, 2009;MCLENON;ROGERS, 2018;REIN-HARD et al, 2021) was not found in our sample. This is likely because our study compared toddlers with preschoolers, while the other studies (KUSHNIR; SA-DEH, 2009;REINHARD et al, 2021) used school children (between six and 11 years old) samples and subdivided them for the comparisons. To endorse that hypothesis, we can argue that fears still unfold in this toddler and preschool age group (KONKABAYEVA et al, 2016;WARREN;OLLENDICK;SIMMENS, 2008).…”
Section: Discussionmentioning
confidence: 99%